Paradox of the Mission of Albanian Political Parties (European Journal of Social Sciences, 2018)
While everyone has a negative opinion on political parties, they are all powerful because, when they win the elections, they all win. They have a paradoxical mission: only political parties can hire anyone who helps them win the election. There are political parties of the majority who "appoint" the President of the Republic. Despite the large number of political parties, as a sign of the country's normal democratization, the parties remain divided into two categories: the main party and the partisans, which survive thanks to the main parties. The worst thing is that the "party equal employment" tradition is being taught, as every member or party militant calls the normal job demand after the victory of political elections by the coalition where his "party". Generally, in Albania there is a negative opinion about political parties, but the high poverty and unemployment, as well as the fact that work finds easier when you join one party and win the elections, have made many people become party members. This has also led to a "pragmatic" view of political coalitions. It is up to the opinion that coalitions are good to be post-election, that parties and party parties should measure their real strength, but also program, so that everyone with a single tongue and within their family.